2016
DOI: 10.4081/monaldi.2008.427
|View full text |Cite
|
Sign up to set email alerts
|

Family history of cardiovascular disease as a risk factor for coronary artery disease in adult offspring

Abstract: These findings indicate that positive family history is a major risk factor for coronary artery disease which strongly predisposes to the atherosclerotic process at younger ages; therefore, these patients should be evaluated and managed more intensively for other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…Meanwhile elevated resting heart rate is known as a CAD risk factor, which is in agreement with our findings (w=0.674) [51]. In the literature, the family history of CAD is a major CAD risk factor in adults [52]. This is in agreement with our findings where it had the highest GMM weight (w=1; Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile elevated resting heart rate is known as a CAD risk factor, which is in agreement with our findings (w=0.674) [51]. In the literature, the family history of CAD is a major CAD risk factor in adults [52]. This is in agreement with our findings where it had the highest GMM weight (w=1; Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…Family history of IHD was identified in 6.4% of the patients ACS. Although, there is a debate about the role of positive family history as an independent risk factor for coronary artery disease, it was reported that, positive family history is a major risk factor for coronary artery disease which intensely predisposes to the atherosclerotic development at younger ages; therefore, these patients should be assessed and managed more intensively for other risk factors [35]. Family history of coronary heart disease (CHD) is a well-established risk factor for CHD.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Meanwhile, studies have revealed that anemia is an important risk factor for CAD-related mortality and morbidity. [5][6][7] Mortality of surgical intervention for coronary artery revascularization is also associated with preoperative anemia.…”
Section: Introductionmentioning
confidence: 99%